The Role of Brand Image Mediate the Influence of E-WOM and Celebrity Endorser on Purchase Intention of Lemonilo Instan Noodle Products - Nurbasari, Anny Nurbasari; Putri, Isabella Monica (PT. Global World Scientific, 2023)
The purpose of this study was to determine and analyze the effect of electronic word of mouth (E-WOM) and celebrity endorsement on purchase intention of Lemonilo instant noodles with brand image as a mediating variable. The sample of this study were all teenagers and adults in the city of Bandung who had never consumed Lemonilo instant noodles. The number of samples is 185 respondents. The results of data processing are carried out using SEM analysis with processing using smart PLS. From the results of hypothesis testing, it was found that there was no positive effect of E-WOM on purchase intention, there was a positive influence of celebrity endorsers on purchase intention, there was a positive effect of E-WOM on brand image, there was no positive influence of celebrity endorsers on brand image, there was a positive influence brand image on purchase intention. For mediating variables, brand image is able to mediate the impact of E-WOM on purchase intention, and brand image is not able to mediate the impact of celebrity endorsers on purchase intention. Thus, the Lemonilo company needs to be able to improve E-WOM, by standardizing the existence of reviews of Lemonilo noodles, and being able to select easily recognizable celebrities for the advertisements used.